2019
DOI: 10.5897/ajar2018.12981
|View full text |Cite
|
Sign up to set email alerts
|

Degradation assessment of wetlands under different uses: implications on soil quality and productivity

Abstract: The assessment of degradation status of wetland soils under five different land use types (LUTs) in Ogun state, Nigeria were studied. The laboratory study was conducted to determine the physical, chemical and biological properties of these wetlands and the results obtained were compared with the food and agriculture organization (FAO) standard indicators and criteria for land degradation assessment. The textural composition of the soil ranged from sandy loam to sandy clay loam. Total porosity was generally low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It can be concluded that most of the above investigations were conducted in China with few studies in East Africa( (Hedman, 2019;Ewing et al, 2012;, Zhao et al, 2020Sun et al, 2011;Wang et al, 2012, Lian et al, 2013Osinuga and Oyegoke, 2019;Arunrat, 2020 andMujiyo et al, 2018). Similarly, none of the above studies determined the effect of cultivation of wetlands on heavy metals and most of the studies concentrated on OM, soil pH and macro nutrients.…”
Section: Wetland Assessment and Effective Managementmentioning
confidence: 99%
“…It can be concluded that most of the above investigations were conducted in China with few studies in East Africa( (Hedman, 2019;Ewing et al, 2012;, Zhao et al, 2020Sun et al, 2011;Wang et al, 2012, Lian et al, 2013Osinuga and Oyegoke, 2019;Arunrat, 2020 andMujiyo et al, 2018). Similarly, none of the above studies determined the effect of cultivation of wetlands on heavy metals and most of the studies concentrated on OM, soil pH and macro nutrients.…”
Section: Wetland Assessment and Effective Managementmentioning
confidence: 99%